2012
DOI: 10.1111/j.1753-0237.2011.00208.x
|View full text |Cite
|
Sign up to set email alerts
|

Country heterogeneity and long‐run determinants of inflation in the Gulf Arab states

Abstract: Applying nonstationary panel data econometric methods, this paper analyzes the major sources and transmission of inflation in the Gulf Cooperation Council (GCC) countries over the 1980-2008 period. We argue that, in GCC countries, money is essentially demand determined, so that the high collinearity between money and aggregate demand indicators such as non-hydrocarbon output is expected and should be dealt with accordingly. Several important results emerge from the analysis. First, the money supply stands out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 43 publications
(70 reference statements)
1
14
0
Order By: Relevance
“…We define inflation dynamics as "a non transitory change in the value, trend and the continuity of inflation over time due to changes in the relative importance of the factors motivating the inflationary process" 5 . Basher and Elsamadisy (2012) investigates the main sources the sources and transmission of inflation in GCC countries over the period 1980-2008 and suggested that inflation in trading partners, money and the nominal effective exchange rate are affecting inflation in the short run and only money is affecting inflation in the long run. Kandil and Morsy (2009) examined the determinants of inflation in GCC countries for the period between 1970 and 2007 and found that inflation in trading partners is very important in affecting inflation, while in the long run public capital spending helps easing inflationary pressures and excess demand is an important determinant in the short run.…”
Section: Literature Reviewmentioning
confidence: 99%
“…We define inflation dynamics as "a non transitory change in the value, trend and the continuity of inflation over time due to changes in the relative importance of the factors motivating the inflationary process" 5 . Basher and Elsamadisy (2012) investigates the main sources the sources and transmission of inflation in GCC countries over the period 1980-2008 and suggested that inflation in trading partners, money and the nominal effective exchange rate are affecting inflation in the short run and only money is affecting inflation in the long run. Kandil and Morsy (2009) examined the determinants of inflation in GCC countries for the period between 1970 and 2007 and found that inflation in trading partners is very important in affecting inflation, while in the long run public capital spending helps easing inflationary pressures and excess demand is an important determinant in the short run.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Most of the studies that use money supplies as inflation predictor, such as those by [12][13][14][15][16][17][18], report a positive relationship between money supply and inflation. For instance, [12] found that higher money supply can prompt inflation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As a result of higher inflation, Qatar's effective exchange rate appreciated over the [2005][2006][2007][2008], as depicted in Figure 3d. See Basher and Elsamadisy (2012) for an empirical analysis on the sources of inflation in GCC countries.…”
Section: Acceleration In Money and Credit Growthmentioning
confidence: 99%